Associations of mobile phone addiction with suicide ideation and suicide attempt: findings from six universities in China - Wenhua Wang; Wenhua Wang; Mingyang Wu; Zhongliang Zhu; Le Ma; Lei Zhang; Lei Zhang; Lei Zhang; Hui Li (Frontiers Media S.A., 2024)
BackgroundMobile phones are becoming indispensable for life and have changed various aspects of people's lives. The psychological impacts of excessive mobile phone use have emerged as an impressive problem among college students. However, little is known about the associations of mobile phone addiction with suicide ideation and suicide attempt.MethodsA cross-sectional study was conducted with students from six universities in 2022. We collected the socio-demographic characteristics, suicide ideation, suicide attempt, psychosocial factors (depressive symptoms, social support, sleep quality), and health-related characteristics (smoking, drinking, body mass index). Mobile phone addiction was ascertained by the Mobile Phone Addiction Tendency Scale (MPATS). The associations of mobile phone addiction with suicide ideation and suicide attempt were estimated using binary logistic regression and restricted cubic splines regression.ResultsA total of 18,723 college students [6,531 males (34.9%) and 12,192 females (65.1%)] were included in the final analysis. Eleven percent of participants had a history of suicide ideation, and 1.8% of participants had engaged in suicide attempt. A total of 5,553 students (29.7%) met the criteria of mobile phone addiction (MPATS score ≥48), and the average score on the MPATS was 39.5 ± 13.0. After adjustment for potential covariates, mobile phone addiction was significantly associated with increased odds of suicide ideation (OR, 1.70; 95% CI, 1.53-1.88) and suicide attempt (OR, 1.48; 95% CI, 1.18-1.86). Gender did not affect the associations of mobile phone addiction with suicide ideation and suicide attempt (P for interaction > 0.05). The restricted cubic splines regression displayed a nonlinear dose-response association between MPATS score and risk of suicide ideation (P for non-linearity < 0.001), while a monotonically increasing risk of suicide attempt was found to be associated with an increasing MPATS score (P for non-linearity = 0.420).ConclusionsMobile phone addiction is associated with suicide ideation and suicide attempt among college students. The findings indicate that early examination, prevention, and intervention for mobile phone addiction may benefit the prevent and control of suicide.